Nuclear and plastid SNP markers for tracing Cedrela timber in the tropics - Paredes-Villanueva, Kathelyn; Blanc-Jolivet, Celine; Mader, Malte; Honorio Coronado, Eurídice N.; Garcia-Davila, Carmen; Sebbenn, Alexandre M.; Rocha Venancio Meyer-Sand, Barbara [UNESP]; Caron, Henri; Tysklind, Niklas; Cavers, Stephen; Degen, Bernd (Springer Nature, 2019)
Illegal logging and trade of timber are major worldwide concerns, resulting in biodiversity and economic losses. Tropical tree species in the genus Cedrela, which have historically been heavily exploited, are still often illegally traded and there is an urgent need to develop tools to verify the origin of Cedrela products. A set of 351 SNP loci for Cedrela species from Bolivia, Brazil, Costa Rica, Cuba, Ecuador, French Guiana, Mexico, and Peru was developed using restriction associated DNA sequencing (RADSeq) and low coverage MiSeq genome sequencing, and adapted for MassARRAY genotyping. After screening of 94 individuals covering most of the distribution of Cedrela, a final set of 136 SNP loci which included 92 nuclear SNPs, 22 chloroplast markers (20 SNPs and 2 INDELs), and 22 mitochondrial markers (19 SNPs and 3 INDELs) was selected and tested for potential to verify Cedrela timber origin.
Keywords: Cedrela; MassARRAY; MiSeq; RADSeq; SNP; Tracing origin; Tropical timber